Comparison of Robotic-Assisted vs. Conventional Laparoscopy for Para-aortic Lymphadenectomy in Gynecological Malignancies: A Systematic Review and Meta-Analysis - Zhou, Zhengli; Ge, Jing; Ye, Kefan; Zhang, Yifeng; Hu, Qian; Wang, Limei; Chen, Yiwen (Frontiers in Surgery, 2023)
Background: Robotic-assisted surgery is one of the novel minimally invasive surgical techniques for the treatment of gynaecological malignancies. The aim of this systematic review and meta-analysis was to compare the outcomes of robot-assisted versus conventional laparoscopy for para-aortic lymphadenectomy (PAL) in patients with gynaecological malignancies. Methods: An electronic search in PubMed, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials), and Google Scholar databases was performed for articles, published up to 01st November 2021. Outcomes including operating time (OT), total blood loss (TBL), length of stay (LOS) and complication rate (CR) in robot-assisted versus conventional laparoscopy were investigated. Results: A total of nine studies (7 non-RCTs and 2 RCTs) involving 914 participants were included. Of them, 332 patients underwent robotic laparoscopy (robotic group) and 582 - a conventional laparoscopy (conventional laparoscopy group). A significant decrease in TBL (MD = −149.1; 95% CI: −218.4 to -79.91) [mL] was observed in the robotic group as compared to the conventional laparoscopy group. However, no significant difference was noted for OT, CR and LOS in the overall findings. Further subgroup analysis showed that the robotic group had a lower OT in mixed histological population and studies reporting on extraperitoneal approach. The lower chance of TBL were observed in mixed histological population and studies involving extraperitoneal approach, Caucasian population and non-RCTs design. Conclusions: Robotic laparoscopy has a significant advantage over the conventional laparoscopy approach for PAL in gynaecological malignancies. Further prospective observational studies embedded with large sample size are needed to validate our findings.